Evidence for a Central Apolipoprotein A-I Domain Loosely Bound to Lipids in Discoidal Lipoproteins That Is Capable of Penetrating the Bilayer of Phospholipid Vesicles - Córsico, Betina (2001)
Previous evidence indicated that discoidal reconstituted high density lipoproteins (rHDL) of apolipoprotein A-I (apoA-I) can interact with lipid membranes (Tricerri, M. A., Córsico, B., Toledo, J. D., Garda, H. A., and Brenner, R. R. (1998) Biochim. Biophys. Acta 1391, 67-78). With the aim of studying this interaction, photoactivable reagents and protein cleavage with CNBr and hydroxylamine were used. The generic hydrophobic reagent 3-(trifluoromethyl)-3-(m-[125I]iodophenyl)diazirine gave information on the apoA-I regions in contact with the lipid phase in the rHDL discs. Two protein regions loosely bound to lipids were detected: a C-terminal domain and a central one located between residues 87 and 112. They consist of class Y amphipathic α-helices that have a different distribution of the charged residues in their polar faces by comparison with class A helices, which predominate in the rest of the apoA-I molecule. The phospholipid analog 1-O-hexadecanoyl-2-O-[9-[[[2-[125I]iodo-4-(trifluoro-methyl-3-H-diazirin-3-yl)benzyl]oxy]carbonyl-] nonanoyl]-sn-glycero-3-phosphocholine, which does not undergo significant exchange between membranes and lipoproteins, was used to identify the apoA-I domain directly involved in the interaction of rHDL discs with membranes. By incubating either rHDL or lipid-free apoA-I with lipid vesicles containing 125I-TID-PC, only the 87-112 apoA-I segment becomes labeled after photoactivation. These results indicate that the central domain formed by two type Y helices swings away from lipid contact in the discoidal lipoproteins and is able to insert into membrane bilayers, a process that may be of great importance for the mechanism of cholesterol exchange between high density lipoproteins and cell membranes.